2020
DOI: 10.1002/chir.23220
|View full text |Cite
|
Sign up to set email alerts
|

Conformational preference of bicyclic β‐amino acid dipeptides

Abstract: Bridged bicyclic amino acids have high potential applicability as self‐organized, conformationally constrained synthetic building blocks that do not require assistance from hydrogen bond formation. We systematically investigated the intrinsic conformational propensities of dipeptides of bridged bicyclic β‐amino acids by means of accelerated molecular dynamics simulation and density functional theory (DFT) calculations in methanol, chloroform, and water. While the main‐chain conformation, represented by φ and θ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It is interesting to note that N -acyl-7-azabicyclo­[2.2.1]­heptanes (Figure ) can be classified as pyramidalized amides (average χ N of 52.0°; average τ of 16.6°). The origin of nitrogen pyramidalization in N -acyl-7-azabicyclo­[2.2.1]­heptanes has been proposed to be due to small C–N–C angle and allylic strain between the amide substituents and the bridgehead hydrogen atoms. In agreement with this hypothesis, increased substitution of 7-azabicyclo[2.2.1]­heptane results in an increase in nitrogen pyramidalization (e.g., 5.20 , χ N of 64.5°) . Rotational barriers of 7-azabicyclo[2.2.1]­heptane amides have been measured and are comparable to N -acyl-azetidines ( 5.12 , 15.0 kcal/mol; N -4-toluoyl-azetidine, 15.7 kcal/mol) .…”
Section: Acyclic Amides: N-pyramidalization 40–60°mentioning
confidence: 87%
See 3 more Smart Citations
“…It is interesting to note that N -acyl-7-azabicyclo­[2.2.1]­heptanes (Figure ) can be classified as pyramidalized amides (average χ N of 52.0°; average τ of 16.6°). The origin of nitrogen pyramidalization in N -acyl-7-azabicyclo­[2.2.1]­heptanes has been proposed to be due to small C–N–C angle and allylic strain between the amide substituents and the bridgehead hydrogen atoms. In agreement with this hypothesis, increased substitution of 7-azabicyclo[2.2.1]­heptane results in an increase in nitrogen pyramidalization (e.g., 5.20 , χ N of 64.5°) . Rotational barriers of 7-azabicyclo[2.2.1]­heptane amides have been measured and are comparable to N -acyl-azetidines ( 5.12 , 15.0 kcal/mol; N -4-toluoyl-azetidine, 15.7 kcal/mol) .…”
Section: Acyclic Amides: N-pyramidalization 40–60°mentioning
confidence: 87%
“…In addition to twisting, amide bond geometric distortion can be achieved by pyramidalization of the nitrogen atom. In the extreme cases, these pyramidalized amides feature sp 3 hybridization that is more characteristic to amines rather than amides. , The most well-known examples of such pyramidalized amides include confining the amide bond nitrogen in a cyclic ring system, such as azetidine or aziridine, however, in these moieties, the inherent ring strain of the small-ring heterocycle contributes to the reactivity of these amides . Recent elegant studies by Ohwada and co-workers identified 7-azabicyclo[2.2.1]­heptane amides (such as 5.7 , Figure ) as another class of fully pyramidalized amides. …”
Section: Cyclic Amides: N-pyramidalization 40–60°mentioning
confidence: 99%
See 2 more Smart Citations